A multiply imaged z ∼ 6.3 Lyman alpha emitter candidate behind Abell 2261 - Rydberg, Claes-Erik; Klessen, Ralf S. (Arxiv, 2016)
While the Lyman-$α$ ($Lyα$) emission line serves as an important tool in the study of galaxies at $z\lesssim 6$, finding Ly$α$ emitters (LAE) at significantly higher redshifts has been more challenging, probably because of the increasing neutrality of the intergalactic medium above $z\sim6$. Galaxies with extremely high rest-frame Ly$α$ equivalent widths, EW(Ly$α$) $\gtrsim 150$ Å, at $z>6$ are good candidates for Ly$α$ follow-up observations, and can stand out in multiband imaging surveys because of their unusual colors. We have conducted a photometric search for such objects in the Cluster Lensing And Supernova survey with Hubble (CLASH), and report here the identification of three likely gravitationally-lensed images of a single LAE candidate at $z\sim6.3$, behind the galaxy cluster Abell 2261